United Kingdom : Hong Kong; Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in the United Kingdom-Hong Kong during 1990, focusing on the expansion and the subsequent slowing in domestic demand in the 1990s, against the background of the export-driven growth in the second half of the 1980s. Developments in aggregate demand and supply, labor and property markets, and inflation and competitiveness are analyzed. The paper reviews budgetary developments, discusses issues in the structure of revenue and expenditure, and describes the proposed Mandatory Provident Fund scheme. Monetary and exchange rate developments are also analyzed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet